Factors Affecting MSMEs Taxpayer Compliance - Vallery Seannanda; Erna Sulistyowati (Universitas KH. Abdul Chalim Mojokerto, 2025)
Tax is the largest source of state revenue in Indonesia. In recent years, MSMEs have made a good contribution to the economy in Indonesia. This has become the focus of the government to explore the tax potential of MSMEs. The purpose of this study is to determine the effect of tax rates, taxpayer awareness, and tax sanctions on MSME taxpayer compliance. There are three independent variables tested, namely tax rates, taxpayer awareness, and tax sanctions. While the dependent variable is MSME taxpayer compliance. The sampling method used is a purposive sample with a sample size of 40 MSME taxpayers. This study uses the Partial Least Square analysis technique assisted by the SmartPLS 3.2.9 application. This research method is quantitative, namely looking for primary data with the object of research being MSME taxpayers registered in Sawahan District, Surabaya City. The results of this study indicate that taxpayer awareness and tax sanctions affect MSME taxpayer compliance. While tax rates do not affect MSME taxpayer compliance.